Nanofluid thermosetting adhesives for bonding forest-based lignocellulosic materials: A Brief Review of Synthesis, characterization, and applications - Muhammad Adly Rahandi Lubis; Lubos Kristak; Petar Antov; Lee Seng Hua (Talenta Publisher, 2025)
various industries, including electrical microchannels, engines, spacecraft,nuclear, and solar energy. Nanofluids are created by floating small nanoparticlesin base fluids such as water or ethylene glycol, with or without stabilizingmethods. The typical size of nanoparticles is less than 100 nm2. Nanofluidthermosetting adhesives have the advantages of enhanced bonding strength,improved thermal conductivity, and reduced curing time. These qualities mightimprove the performance of thermosetting adhesives, which harden or set whenheated. However, the creation of such adhesives would necessitate variousdisadvantages, such as high cost of production and potential health andenvironmental risks. Understanding the physicochemical mechanism of usingnanofluids in the adhesive would be critical. This would include examining theeffects of particle size, shape, surfactant, temperature, etc. on thermalconductivity. While developing nanofluid thermosetting adhesives offers greatopportunities, it also requires overcoming several technical hurdles. Further studyin this area may lead to the creation of adhesives with improved thermal andadhesive qualities. Applications of nanofluid adhesives might cover a broad areaof the wood industry, particularly furniture manufacturing and wooden flooring.This study reviewed possible methods of synthesizing, characterization, andapplications of nanofluid thermosetting adhesives for wood-based composites.